Standardization and Quality Control - the Mandatory Requirement of Herbal Drug Industries - Mehrotra, Shanta (Indian Forester, 2003)
The Ministry of Health and Family Welfare (Department of ISM&H) New Delhi has notified on 23rd June 2000 that the Ayurveda , Siddha and Unani/Pharmacoepial industries should get the certificate of GMP under ’155-B in Schedule I certified of GMP of ASU drugs’ in order to get the license for manufacturing. This rule will be enforced from July 2003. Hence due to the implication of this law the quality evaluation and standardization will be mandatory for all manufacturing units of ASU drugs. A significant percentage of people are using traditional medicine , and the expenditure on these medicine is increasing day by day. Although global market in herbal drugs is over US 60 billion per year but India’s share is very poor , due to lack of quality control and standardization measures. If India’s share has to be increased , a grand strategic plan , particularly in standardization and quality control of herbal drugs should be introduced which may boost up the export to Rs. 10 ,000 crores by 2010. Thus detailed pharmacognostic evaluation is highly essential and is a necessary prerequisite. In this context the National Botanical Research Institute is engaged in standardization and quality control of herbal drugs using different parameters viz. botanical , physical , phytochemical and biological. Besides , other aspects like seasonal variations studies , assessment of microbial loads , shelf life studies , detection of heavy metals and validation of classical and ethnobotanical claims have also been undertaken and more than , 150 single herbal drugs and 20 herbal formulations have been evaluated by the NBRI.